Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1158/1535-7163.mct-06-0587
|View full text |Cite
|
Sign up to set email alerts
|

The RET oncogene is a critical component of transcriptional programs associated with retinoic acid–induced differentiation in neuroblastoma

Abstract: Differentiation is a key feature in pathologic classification and prognosis of neuroblastic tumors, although the underlying molecular mechanisms are not well defined. To identify key differentiation-related molecules and path-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 48 publications
4
40
0
Order By: Relevance
“…Notably, the most significantly enriched functional categories (P < 0.05) upon CHAF1A silencing are associated with multiple processes involved in neuronal differentiation (axonogenesis, synaptic transmission, cell-cell signaling, catecholamine biosynthesis, and nervous system development; Table 2), validating CHAF1A as a potential critical regulator of neuronal differentiation. Furthermore, these functional categories were distinct from the ones described to be enriched in neuroblastoma-cell differentiation upon Cyclin D1 and Cdk4 silencing (29) or retinoic acid treatment (30), suggesting a distinctive mechanism for CHAF1A in inducing cell differentiation (Supplementary Tables S1 and S2). In addition, GSEA revealed that genes regulated by CHAF1A were associated with major metabolic and oncogenic pathways.…”
Section: Chaf1a Silencing Induces Neuronal Differentiation Pathways Amentioning
confidence: 94%
“…Notably, the most significantly enriched functional categories (P < 0.05) upon CHAF1A silencing are associated with multiple processes involved in neuronal differentiation (axonogenesis, synaptic transmission, cell-cell signaling, catecholamine biosynthesis, and nervous system development; Table 2), validating CHAF1A as a potential critical regulator of neuronal differentiation. Furthermore, these functional categories were distinct from the ones described to be enriched in neuroblastoma-cell differentiation upon Cyclin D1 and Cdk4 silencing (29) or retinoic acid treatment (30), suggesting a distinctive mechanism for CHAF1A in inducing cell differentiation (Supplementary Tables S1 and S2). In addition, GSEA revealed that genes regulated by CHAF1A were associated with major metabolic and oncogenic pathways.…”
Section: Chaf1a Silencing Induces Neuronal Differentiation Pathways Amentioning
confidence: 94%
“…Studies have demonstrated that RET is required for retinoic acid-induced neuroblastoma differentiation [158], and that RET inhibition is effective in neuroblastoma preclinical models [159]. Other recent studies have identified the polo-like kinase 1 (PLK1) as a potential target for neuroblastoma therapy, based on screens of a library of kinase inhibitors in neuroblastoma preclinical models [160], while a screening study using an siRNA library identified the checkpoint kinase 1 (CHK1) as a potential target [161].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…It is considered to be an embryonic tumor arising from immature cells of the neural crest, probably due to genetic and molecular alterations that result in arrested cell differentiation and uncontrolled proliferation. In general, neuroblastic tumors are characterized by extreme clinical and pathological heterogeneity (32). The induced differentiation of tumor cells is regarded to be therapeutically advantageous, since more extensively differentiated neuroblastic tumors are usually associated with lower stage and better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The induced differentiation of tumor cells is regarded to be therapeutically advantageous, since more extensively differentiated neuroblastic tumors are usually associated with lower stage and better clinical outcome. Therefore, differentiating agents such as retinoic acid, which is known to induce differentiation in several tumor types including neuroblastoma, have become a part of the therapeutic arsenal (10)(11)(12)20,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation